Revitalisasi Pendidikan Islam Humanis dalam Menanggapi Isu-isu Global Kontemporer: Telaah Al-Quran dan Sunnah - Saidina, Muhammad Farhan (Yayasan Albahriah Jamiah Indonesia, 2025)
Amidst the complexity of contemporary global issues, such as humanitarian crises, intolerance, moral degradation, and value disorientation, Islamic education faces a major challenge to remain relevant and provide effective solutions. Revitalizing Islamic education with a humanist approach is an urgent need to respond to global dynamics that threaten universal human values. This study aims to re-examine the values of Islamic humanism derived from the Qur'an and Sunnah, and to reconstruct an Islamic education model that fosters an empathetic, tolerant, and inclusive attitude in the current context. This study uses a qualitative method with a thematic-analytical approach to the verses of the Qur'an and the hadiths of the Prophet that contain humanist values. The results of the study show that the Qur'an and Sunnah contain fundamental principles of humanist education such as respect for human dignity, justice, compassion, and strengthening noble morals. These principles need to be revitalized through a curriculum, learning methods, and a contextual Islamic educational environment. In conclusion, humanist Islamic education is not just a normative discourse, but a strategic solution in building a just and humane global civilization. The reaffirmation of humanist Islamic values ​​is a middle way between the idealism of revelation and the dynamic global social reality.